Estimação de canais rádio móveis por intermédio de sondas empregando equalizadores adaptativos - Ferreira, Carlos Eduardo Salles (2008)
The mobile radio channel characterization is essential to design mobiles wireless telecommunication systems and equipments. The theoretical time variant radio channel model is well characterized in the time and frequency domains, considered as wide-sense stationary, uncorrelated scatterings (WSSUS) channel and, for a particular environment, it is necessary to make field measurements to obtain real data results. To accomplish this task, known as mobile radio channel sounding, there are some well studied methods. In this work, a new wideband channel sounding method that uses adaptive filter theory (equalization devices) to obtain an estimated channel on unknown environment is proposed. Several simulations were done using Matlab tools, for two different typical outdoor channels with different Doppler maximum spread frequencies and several signal to noise ratios. The obtained results by these simulations were compared with those obtained with the swept time-delay cross-correlation (STDCC) method. The conclusions of the results comparison show that, equalizer sounding method presents a channel estimation close to the reference channel, and is equivalent to that obtained by STDCC sounding technique